Pengaruh Budaya Organisasi Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan Cv. Abankirenk Yogyakarta - Andini Aulia Tasya; Alvionita Alvionita; Naurah Amirah Suben (Trending: Jurnal Manajemen dan Ekonomi, 2023)
This study aims to determine: (1) The effect of organizational culture on job satisfaction of CV employees. Abankirenk Yogyakarta, (2) How does the influence of work motivation on job satisfaction of employees at CV. Abankirenk Yogyakarta, and (3) The influence of organizational culture and work motivation on job satisfaction of CV employees. Abbankiren Yogyakarta. This research is included in the causal associative research with a quantitative approach methodology. The population in this study is 60 people who are employees of Abankirenk. This study uses population research. Questionnaires that have received reliability and validity tests are used to collect data. Multiple regression is a technique used for data analysis. The research findings at a significance level of 5% indicate that (1) corporate organizational culture has a positive and significant effect on employee job satisfaction, as indicated by the beta coefficient (β) 0.278 (p = 0.000), and (2) work motivation has a positive and significant effect on Job satisfaction is indicated by a beta coefficient (β) of 0.250 (p=0.001), (3) company organizational culture and work motivation have a positive and significant effect on employee job satisfaction as indicated by a beta coefficient (β) on organizational culture variable of 0.222 (p = 0.004) and 0.187 (p = 0.010), and the contribution of work motivation has a positive effect on job satisfaction (p = 0.001) and (R2) 0.046. Contribution of influence (R2) 0.077 organizational culture and work motivation on job satisfaction